Perkembangan Pemikiran Politik Islam Dari Masa Klasik Hingga Kontemporer - -, Hafsa; Najibuddin, Muhammad; Hamidah, Zulfa; Febriani, Sari (The International Journal of Pegon : Islam Nusantara civilization, 2025)
Perkembangan Pemikiran Politik Islam dari Zaman Klasik hingga Zaman Kontemporer: Pemikiran politik dalam Islam merupakan elemen penting dalam tradisi intelektual Islam yang membahas gagasan-gagasan fundamental tentang pemerintahan, seperti keadilan, kepemimpinan, syura (musyawarah), dan penerapan hukum Islam dalam konteks kenegaraan. Sejak zaman Nabi Muhammad SAW hingga kini, pemikiran ini terus berkembang seiring dengan perubahan sosial dan politik di kalangan umat Islam. Tokoh-tokoh seperti Al-Mawardi, Al-Farabi, Ibnu Khaldun, Hasan Al-Banna, dan Abul A'la Al-Maududi telah memberikan kontribusi yang signifikan dalam merumuskan sistem politik ideal dari perspektif Islam. Di era modern, pemikiran politik Islam berupaya menjawab tantangan global seperti demokrasi, sekularisme, dan isu-isu kepemimpinan, serta menawarkan sistem alternatif yang berbasis pada nilai-nilai moral dan keadilan sosial. Penelitian ini bertujuan untuk memahami evolusi, prinsip-prinsip dasar, dan relevansi pemikiran politik Islam dalam menghadapi isu-isu politik terkini. The development of Islamic political thought from classical to contemporary times: Political thought in Islam is an important element in the Islamic intellectual tradition that discusses fundamental ideas about governance, such as justice, leadership, shura (deliberation), and the application of Islamic law in the context of the state. Since the time of the Prophet Muhammad SAW until now, this thought has continued to develop along with social and political changes among Muslims. Figures such as Al-Mawardi, Al-Farabi, Ibn Khaldun, Hasan Al-Banna, and Abul A'la Al-Maududi have made significant contributions in formulating an ideal political system from an Islamic perspective. In the modern era, Islamic political thought seeks to answer global challenges such as democracy, secularism, and leadership issues, and offers an alternative system based on moral values and social justice. This study aims to understand the evolution, basic principles, and relevance of Islamic political thought in dealing with current political issues.